Pengaruh Time Budget Pressure, Risiko Audit, dan Kompleksitas Audit terhadap Kualitas Audit - Aidil, Agnes Wal; Halmawati (Jurnal Nuansa Karya Akuntansi, 2026)
This study aims to analyze the effect of time budget pressure, audit risk, and audit complexity on audit quality. This research uses a quantitative approach. Primary data was collected using a questionnaire and the research sample consisted of auditors who worked at the Public Accounting Firm in Padang City, the sampling technique used total sampling. The hypothesis was tested using multiple linear analysis with SPSS 30. The results showed that time budget pressure and audit complexity had a negative effect on audit quality. While audit risk has no effect on audit quality. For future research is expected to expand the research population and add other variables that are not in this study.